Common core : using global children's literature and digital technologies - Saine, Paula (Rowman & Littlefield, 2016)
"Common Core is an instructive book that enhances classroom teacher knowledge-base of global and multicultural literature texts, which as a result, deepens student appreciation for cultures around the world. Through use of technology and multicultural literature, Dr. Saine fires up the imagination of students, as she transports them to other cultures, countries and regions of the world. It is a highly nuanced text that builds bridges across cultures while meeting English Language Arts (ELA) standards. The text is likely to make a lasting contribution to this mostly neglected area of student cultural awareness and development"--Provided by publisher